Asthma-related mortality after release from prison: a retrospective data linkage study. (2nd January 2023) - Forsyth, Simon; Alati, Rosa; Kinner, Stuart A.
Abstract: Background: People who experience incarceration are at increased risk of asthma and have a higher prevalence of risk factors associated with asthma-related mortality. However, there has been little research on the relationship between asthma and mortality in people released from prison. Objectives: This study examined the association between asthma and all-cause and cause-specific mortality, and estimated the increased risk of asthma-related mortality among adults released from prison compared to the age- and sex-matched general population. Design: We used data from a nested case-control sample ( N  = 1658) within a retrospective cohort study of all adults released from prisons in Queensland, Australia, from 1994 to 2007 ( N  = 42015). Deaths were identified using linkage to national mortality records. Nested study cases were sampled from deaths, with a matched control from the cohort. We examined medical and case management records to identify risk factors potentially associated with mortality. Asthma-related mortality in the cohort was compared to that of the matched general population of Queensland. Results: People released from prison were more likely than their age and sex matched general population counterparts to have an asthma-related death (HR = 3.32 95%CI:2.14-5.16). Those who had been identified as having asthma in prison had increased odds of mortality from all-cause (OR = 1.86 95%CI:1.40-2.47), drug-related (OR = 2.5 95%CI:1.40-4.46), cardiovascular-related (OR = 3.2 95%CI:1.57-6.51), and respiratory-related (OR = 3.30 95%CI:1.63-6.70). Conclusion: Among people exposed to incarceration, those with asthma are at elevated risk of death after release from custody. Improved management of respiratory disease in this population may contribute to reducing their high rate of preventable mortality.